Pengembangan Kapasitas Pengelola Perikanan WPP 718 di Kabupaten Merauke: THE CAPACITY BUILDING OF FISHERIES MANAGER WPP 718 RELATED TO EAFM: LEARNING IN MERAUKE DISTRICT - James Abrahamsz (Politeknik Kelautan dan Perikanan Sorong, 2023)
The purpose of this service activity is to conduct EAFM training in order to increase the capacity of fisheries management institutions in Merauke Regency to increase knowledge and understanding related to EAFM and the use of EAFM assessment methods to support fisheries management in FMA 718. This training activity was carried out on 22 – 27 November 2021 which grouped into 4 stages, namely (1). Pre-test at the beginning of the training and post-test at the end of the training to measure the level of knowledge and absorption of the material by participants; (2). Presentation of EAFM materials and discussions between presenters and participants; (3). Field trips and data collection training; (4). Analysis and recommendations as well as presentation of results and discussion. The results obtained from service activities include the training process running and scheduled well and the participants, who, although quite diverse in educational and work backgrounds, are very interested and enthusiastic. The results of the pre-test and post-test assessments showed that on average, participants experienced an increase in knowledge related to EAFM and EAFM assessment methods by 50%.